Patient-reported outcomes with olaparib plus abiraterone versus placebo plus abiraterone for metastatic castration-resistant prostate cancer: a randomised, double-blind, phase 2 trial. Issue 10 (October 2022) - Saad, Fred; Thiery-Vuillemin, Antoine; Wiechno, Pawel; Alekseev, Boris; Sala, Nuria; Jones, Robert; Kocak, Ivo; Chiuri, Vincenzo Emanuele; Jassem, Jacek; Fléchon, Aude; Redfern, Charles; Kang, Jinyu; et al.
Summary: Background: Results of this double-blind, phase 2 trial showed patients with metastatic castration-resistant prostate cancer given olaparib plus abiraterone versus placebo plus abiraterone had significantly improved progression-free survival. Here, we present an exploratory analysis of pain and health-related quality of life (HRQOL). Methods: This double-blind, randomised, placebo-controlled, phase 2 trial was conducted across 41 urological oncology sites in 11 countries in Europe and North America. Eligible patients were aged 18 years or older, had metastatic castration-resistant prostate cancer, and had previously received docetaxel and up to one additional line of previous chemotherapy. Metastatic castration-resistant prostate cancer was defined as increasing prostate-specific antigen (PSA) concentration or other signs of disease progression despite androgen-deprivation therapy and serum testosterone concentrations at castrate levels (≤50 ng/dL), and with at least one metastatic lesion on bone scan, CT, or MRI. Eligible patients were randomly assigned (1:1) to receive oral olaparib (300 mg twice per day) plus oral abiraterone (1000 mg once a day) and oral prednisone or prednisolone (5 mg twice a day) or placebo plus abiraterone (1000 mg once a day) and prednisone or prednisolone (5 mg twice a day). Randomisation was done without stratification and by use of an interactive voice or web response system. A randomised treatment kit ID number was assigned sequentially to each patient as they became eligible. The primary endpoint (radiographic progression-free survival) has previously been reported. HRQOL was a prespecified exploratory patient-reported outcome. Patients were asked to complete the Brief Pain Inventory-Short Form (BPI-SF), single-item worst bone pain, Functional Assessment of Cancer Therapy-Prostate (FACT-P) questionnaire, and EuroQol-5 five-dimension five level (EQ-5D-5L) assessment at baseline, at weeks 4, 8, and 12, then every 12 weeks until treatment discontinuation. Prespecified outcomes were change from baseline in BPI-SF worst pain, single-item worst bone pain and FACT-P Total Outcome Index (TOI) scale scores, time to deterioration in BPI-SF worst pain and worst bone pain, and assessment of the EQ-5D-5L pain and discomfort domain. All analyses were exploratory and done in the full analysis set (all randomly assigned patients, including patients who were randomly assigned but did not subsequently go on to receive study treatment), with the exception of mean baseline and total change from baseline analyses, for which we used the population who had a valid baseline and at least one post-baseline assessment. This trial is registered with Clinicaltrials.gov, NCT01972217, and is no longer recruiting patients. Findings: Between Nov 25, 2014, and July 14, 2015, 171 patients were assessed for eligibility. 29 patients were excluded, and 142 were enrolled and randomly assigned to receive olaparib and abiraterone (n=71) or placebo and abiraterone (n=71). Data cutoff was Sept 22, 2017. Median follow-up was 15·9 months (IQR 8·1–25·5) in the olaparib plus abiraterone group and 24·5 months (8·1–27·6) in the placebo plus abiraterone group. Questionnaire compliance was generally high (43–100%). Least-squares mean changes from baseline in BPI-SF worst pain, single-item worst bone pain, and FACT-P TOI remained stable across all visits for patients in both treatment groups. Adjusted mean change in FACT-P TOI from baseline across all visits was −0·10 (95% CI −2·50 to 2·71) in the olaparib plus abiraterone group and −1·20 (−4·15 to 1·74) in the placebo plus abiraterone group (difference 1·30, 95% CI −2·70 to 5·30; p=0·52). Time to deterioration in pain was similar in both groups (BPI-SF worst pain HR 0·90 [95% CI 0·62–1·32], p=0·30; worst bone pain HR 0·85 [0·59–1·22], p=0·18). Improvement rates in the pain and discomfort domain of the EQ-5D-5L were similar in both groups from baseline to week 48, beyond which a higher proportion of patients in the olaparib plus abiraterone arm reported an improvement compared to the placebo plus abiraterone group. Interpretation: In these prespecified exploratory analyses, there was no significant difference in pain or HRQOL when olaparib was added to abiraterone. In this phase 2 trial, a statistically significant radiographic progression-free survival benefit was observed with the olaparib plus abiraterone combination. These results suggest that the improved survival benefits observed when combining olaparib with abiraterone does not result in different HRQOL compared with placebo plus abiraterone. Phase 3 studies are required to validate these results. Funding: AstraZeneca and Merck Sharp & Dohme, a subsidiary of Merck & Co, Rahway, NJ, USA.